2013
DOI: 10.1016/j.cell.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 11 Is a Circulating Factor that Reverses Age-Related Cardiac Hypertrophy

Abstract: Summary The most common form of heart failure occurs with normal systolic function and often involves cardiac hypertrophy in the elderly. To clarify the biological mechanisms that drive cardiac hypertrophy in aging, we tested the influence of circulating factors using heterochronic parabiosis, a surgical technique in which joining of animals of different ages leads to a shared circulation. After 4 weeks of exposure to the circulation of young mice, cardiac hypertrophy in old mice dramatically regressed, accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
932
5
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 825 publications
(979 citation statements)
references
References 39 publications
33
932
5
9
Order By: Relevance
“…Some anti-ageing molecules, such as growth and differentiation factor 11, granulocyte-macrophage colony stimulating factor, and metalloproteinase inhibitor 2, have been identified in blood from young mice and in human umbilical cord plasma 66,67 . Whether levels of these anti-ageing molecules are reduced in patients with AD, and whether they are pathophysiologically relevant to this disease, remain unknown.…”
Section: Blood Abnormalitiesmentioning
confidence: 99%
“…Some anti-ageing molecules, such as growth and differentiation factor 11, granulocyte-macrophage colony stimulating factor, and metalloproteinase inhibitor 2, have been identified in blood from young mice and in human umbilical cord plasma 66,67 . Whether levels of these anti-ageing molecules are reduced in patients with AD, and whether they are pathophysiologically relevant to this disease, remain unknown.…”
Section: Blood Abnormalitiesmentioning
confidence: 99%
“…found that the muscle and liver from the aged partner of the heterochronic pairs exhibited youthful levels of regeneration (Conboy et al., 2005). A similar “rejuvenating” effect of young blood has been demonstrated in other organs, including the spinal cord (Ruckh et al., 2012), heart (Loffredo et al., 2013), brain (Katsimpardi et al., 2014) (Villeda et al., 2014), β‐cells (Salpeter et al., 2013), and hair follicles (Keyes et al., 2013). Collectively, these observations suggest that exposure to a “young” environment could prevent or reverse age‐dependent decline in the function of critical organ systems.…”
Section: Introductionmentioning
confidence: 99%
“…5 The hair follicle, which cycles through telogen (resting), anagen (growing), and catagen (regression) throughout the life of mammals, undergoes obvious age-related changes including hair loss. 6 The hair follicle contains hair-follicle-associated pluripotent (HAP) stem cells, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] which may also deteriorate during aging.…”
Section: Introductionmentioning
confidence: 99%